Secretary chooses city work - Ferrendelli, Betta (Raton Range Raton, New Mexico, 1992)
Newspaper article on Pam Horn's decision to take the Raton city manager Secretary position.
Master list item #: 11
File location is in the Raton file Cabinet
Keywords: Horn, Pam; Chelewski, Ray; Obrey, Mike; Honeyfield, Eric; Berry Scott; Graham, Alexander; Raton City Manager; FFA Program; Raton Public Schools; Sugarite Mine; Fire Department; Calvary Baptist Church; Local History; Biography; Secretary; Summer projects; City Manager; City Engineer; Grants; Telephone; Street and sanitation; Raton, New Mexico